International Management: Managing in a Diverse and Dynamic Global Environment - V. Phatak Arvind (Mc Graw Hill, 2005)
International Management: Managing in a Diverse and Dynamic Global Environment offers a modern perspective of international management rooted in a recognized framework. The framework follows the generally accepted course structure beginning with the macro-environment, then moves to the firm level, and concludes with the individual manager in the international setting. This traditional framework is embellished with modern chapters on collaborative strategies, managing technology and knowledge, and ethics and corporate social responsibilty. Each chapter has several mini-case examples and full-length, comprehensive cases conclude each part.